2022
DOI: 10.1130/b36404.1
|View full text |Cite
|
Sign up to set email alerts
|

Guide for interpreting and reporting luminescence dating results

Abstract: The development and application of luminescence dating and dosimetry techniques have grown exponentially in the last several decades. Luminescence methods provide age control for a broad range of geological and archaeological contexts and can characterize mineral and glass properties linked to geologic origin, Earth-surface processes, and past exposure to light, heat, and ionizing radiation. The applicable age range for luminescence methods spans the last 500,000 years or more, which covers the period of moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 169 publications
(255 reference statements)
1
5
0
Order By: Relevance
“…The age of sample 6-collected at a depth of 10.31 m from the bottom of the L 1-3 S 1 layer-was 71.5 ± 4.36 ka (D e = 277.26 ± 4.92 Gy), which was in agreement with the age (71 ka) of L 1 /S 1 boundary within the margin of error [4]. Several papers had suggested that a reliable quartz OSL D e value for loess distributed in China is around ~230 Gy (or lower than 300 Gy) and that the saturation age is around ~100 ka [9,57,58]. Two quartz samples-L 1-3 S 2 and middle S-have D e values higher than 300 Gy.…”
Section: Soil Morphological Characteristics Of the Djg Sectionsupporting
confidence: 79%
See 2 more Smart Citations
“…The age of sample 6-collected at a depth of 10.31 m from the bottom of the L 1-3 S 1 layer-was 71.5 ± 4.36 ka (D e = 277.26 ± 4.92 Gy), which was in agreement with the age (71 ka) of L 1 /S 1 boundary within the margin of error [4]. Several papers had suggested that a reliable quartz OSL D e value for loess distributed in China is around ~230 Gy (or lower than 300 Gy) and that the saturation age is around ~100 ka [9,57,58]. Two quartz samples-L 1-3 S 2 and middle S-have D e values higher than 300 Gy.…”
Section: Soil Morphological Characteristics Of the Djg Sectionsupporting
confidence: 79%
“…Later, the samples were soaked in 35% fluorosilicate for about 2-5 days and washed with warm HCl (10%) to remove the precipitated fluorides for purifying quartz grains (90-125 µm). Lastly, the purified quartz grains were fixed in the center area of the 9.7 mm diameter stainless steel discs using silicone oil to determine the equivalent dose (D e ) [57,58].…”
Section: Osl Soil Age Dating 231 Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The goodness-of-fit of the SGC can be evaluated using the In previous papers the agreement of SAR and SGC results was based on their De values ± their 2 σ standard error (e.g., Li et al, 2015a,b;Sontag-González et al, 2021). When reporting luminescence ages the 1 σ standard error is commonly used (Mahan et al, 2022). The De values had average RSEs of ~16 %, therefore the agreement within 1 σ seems inappropriate to evaluate the differences between the SAR procedure and the SGC method.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was divided In the laboratory under safe light conditions for equivalent dose (D e ) and dosimetry (D r ) measurements. Quartz grains were extracted for OSL measurements following standard sample preparation techniques (see [43,44]). Organic matter and carbonates were removed using H 2 O 2 and HCl, respectively, before the 180-212 µm quartz fraction was isolated by dry sieving and density separation using a solution of sodium polytungstate at 2.70 g.cm − 3 and 2.63 g.cm − 3 .…”
Section: Methodsmentioning
confidence: 99%